Projecting the energy pathway using a methodological sequence: The case of Mexico. (December 2019) - Livas-García, A.; Bonilla, D.; Escalante Soberanis, M.A.; Bassam, A.
Abstract: The relationship between primary energy and economic development tends to be positive; however, it is a complex relationship for emerging economies. We use the energy pathway ( EP ) method to 1) examine this relationship, 2) introduce its behavioural taxonomy and 3) propose a hybrid methodological sequence, that allows to examine the historical context and to forecast the EP . We apply our methodology to the Mexican case, an emerging economy that has had both energy-intensive and energy-productivity periods, and changes in its development model. The study was conducted by using data of a 52-year-old path and explored the path may have from 2018 onwards. Our results are as follows. First the pathway shows nine behavioural possibilities. Second, we found that the Mexican EP responds to structural changes. We conclude that for the years following 2018, Mexico's path will have a disturbance, the main objective will be to avoid unwanted behaviour. The key is to improve the relationships among the government, the private sector and international agreements. In order to continue the sequence of the theory on the relations between energy and development, more studies are needed under a systematic analytical framework, applied to both other countries and comparative studies. Highlights: A theoretical analysis on relationship between energy and economic development process is exposed. The Energy Pathway analysis used by international energy agencies is extended. Modifications in the development model and alternation disturbed the Mexican Energy Pathway. Causes and implications related with a sequence of energy pathway scenarios are presented.